Sediment Metal Contamination, Bioavailability, and Oxidative Stress Response in Mangrove Avicennia marina in Central Red Sea - Alhassan, Abdullahi Bala; Aljahdali, Mohammed Othman (Frontiers in Environmental Science, 2021)
Anthropogenic activities have been on the increase in the urban environment and have led to contamination of the environment with toxic metals. However, mangrove plants’ response to heavy metal stress due to anthropogenic activities explains the metal bioavailability and its potential ecotoxicological effect. We carried out a multi-approach study to investigate i) if the concentrations of metals (Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Mo, Cd, Pb, Sr, and V) in mangroves at the central Red Sea are due to the anthropogenic influence and are above the sediment quality guidelines and ii) if an increase in metal concentration influences height and antioxidant enzyme (catalase, CAT; glutathione S-transferase, GST; and superoxide dismutase, SOD) activities in Avicennia marina. There were significant variations (p < 0.05) in metal concentrations and antioxidants across the six mangrove ecosystems with higher concentrations at Al Lith (LT) and south Jeddah (SJ). Even though the concentrations of metals in mangrove leaves are slightly higher in LT than SJ, principal component analysis showed that higher concentrations of Cr, Co, Zn, Cd, and Pb in mangrove leaves from SJ influence higher antioxidant enzyme activities and the lowest average mangrove height (2.01 m). This suggests that higher metal concentrations be factors for the biggest stress in these mangrove ecosystems. However, among the 13 metals, Cr (82.07 mg/kg), Cu (41.29 mg/kg), and As (10.30 mg/kg) in sediments have values within the ERL range of probable effect, while Ni (53.09 mg/kg) was above the ERM threshold. Hence, there is need to focus on monitoring these metals in mangrove sediments and their anthropogenic sources.